Strategy for Developing Marinated Catfish (Clarias gariepinus) Products in Depok City, West Jawa - Cahaya Gumelar, Faisal; Lailatul Mubarokah, Syaima; Kusumawati, Riny (FAKULTAS PERTANIAN UNIVERSITAS RATU SAMBAN, 2025)
The purpose of this study is to analyze the performance of marinated catfish businesses, identify internal and external factors that influence the marketing of these products, and formulate development strategies that can be applied by UMKM actors. This study uses primary data obtained through open interviews with the help of questionnaires and direct observation of marinated catfish UMKM actors in Depok City. In addition, secondary data was collected from various relevant literature sources. Respondents were selected using purposive sampling, involving three UMKM, namely LESIGO, Gerai D'Pita, and Terra Farm. The development strategy analysis was conducted descriptively and quantitatively using the SWOT Analysis method. The results of the IFE Matrix analysis showed a value of 2.52 for Lesigo UMKM, 2.66 for Gerai D'Pita, and 2.56 for Terra Farm. This indicates that internally, Gerai D'Pita is in a strong position, so it is recommended to utilize internal strengths as the main capital in facing competition. Meanwhile, Lesigo and Terra Farm are in an average position, which means that both UMKM need to optimize their potential and strengths. Meanwhile, the EFE Matrix results show a value of 3.21 for Lesigo, 3.61 for Gerai D'Pita, and 3.16 for Terra Farm. These values indicate that externally, the three marinated catfish UMKM in Depok City are in a position above.